Application of the Chi-Square Automatic Interaction Detection (CHAID) Method in Analysing Variables That Influence Drug Abuse in Province North Sumatera - Yuda, Muhammad Wira; Widyasari, Rina; Aprilia, Rima (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The aim of this research is to classify transmission variables in North Sumatera Province using the Chi-Square Automatic Interaction Detection (CHAID) method. This method is used to determine which factors are the most dominant that cause people in North Sumatra Province to use drugs. This research began with collecting data on drug users in North Sumatra Province taken from BNN PROVSU. After the data was collected, it was processed again using MS Excel and divided into the 6 most dominant factors in the data that trigger drugs. Then, using the SPSS application, calculate which factors are the most dominant that cause people in North Sumatra to use drugs. Based on research conducted by the author on drug abuse in North Sumatra Province using the CHAID method, conclusions can be drawn as follows: The most dominant factor causing people in North Sumatra Province to use drugs is the educational factor. Of the total values that have been examined using the chi-square method, they are X3 (educational factor) with a value = χ² count (13,018) > χ² Table (9,488). Education Factors of Drug Abuse in North Sumatra Province Associated with the Ratio of Narcotics Users.